Analisis Kemampuan, Pengalaman dan Motivasi Melalui Produktivitas Tenaga Kerja pada Proyek Pembangunan Gedung Kantor Bahasa Provinsi Maluku - Wattimena, Angel C; Leuhery, Lenora; Langi, Jeffrey Payung (JURNAL ILMIAH NUSANTARA, 2025)
The success rate of a construction project depends on labor productivity. Construction project labor is required to work effectively, efficiently and is expected to be in accordance with the plans that have been made. However, in reality found in the field, it is still less effective at work. This study aims to determine the effect of work ability, work experience and work motivation on labor productivity in the Construction of Maluku Province Language Building. In the field data collection is done by direct observation, while for the calculation of work volume using excel calculations. This research was also conducted by distributing questionnaires to the workforce to find out the factors that affect labor productivity. Questionnaire data was processed using SPSS version 25. From the results of the study, it was found that the volume of light brick installation work on labor productivity. Then obtained a total overall average of 15.9375 m2 / day. From the results of SPSS analysis obtained factors affecting labor productivity in the installation of lightweight bricks in the Construction of Language Building Maluku Province shows that the coefficient of determination (R2) value of 0.911. This means that 91.1% of the dependent variable in the form of work productivity in the construction of the language office building can be influenced by the variables of work ability, work experience and work motivation while the remaining 8.9% is influenced by other variables not included in this study.